Artificial Intelligence and the Challenge of Protecting Privacy in Legal Consultancy Services in Viet Nam - Tai, Tran Phu (VNU Journal of Science: Legal Studies, 2026)
Artificial Intelligence (AI) has been generating numerous opportunities for innovation in the field of legal consultancy, particularly through digital platforms and automated support systems. However, the deepening integration of AI into the processes of handling, analyzing, and storing legal information simultaneously poses significant challenges to the protection of privacy, a fundamental human right enshrined in international treaties and Vietnamese law. This article, adopting a human rights-based approach, analyzes the potential privacy risks associated with the use of AI in legal consultancy services. These risks include the collection, processing, and storage of sensitive personal data, lack of transparency in data handling, potential information leakage, and the absence of effective mechanisms for accountability and oversight. Through an examination of AI-based legal consultancy models implemented in several countries, and a comparison with the current practices in Vietnam, the article identifies existing legal gaps - particularly regarding the regulation of legal liability for system operators, the enforcement of ethical standards in technology deployment, and the protection of personal data in digital legal consultancy environments. The paper aims to contribute to the development of a modern legal framework that not only promotes innovation but also ensures the robust protection of fundamental human rights.